Dose selection for a phase III study evaluating gepotidacin (GSK2140944) in the treatment of uncomplicated urogenital gonorrhoea. (21st November 2022) - Scangarella-Oman, Nicole E; Hossain, Mohammad; Perry, Caroline R; Tiffany, Courtney; Powell, Marcy; Swift, Brandon; Dumont, Etienne F
Abstract : Background: Gepotidacin is a novel, first-in-class triazaacenaphthylene antibiotic that inhibits bacterial DNA replication by a distinct mechanism of action and is active against most strains of Neisseria gonorrhoeae ( N. gonorrhoeae ). Phase II data suggested higher exposures were needed for efficacy and to suppress resistance development. A translational approach using in vitro pharmacokinetic/pharmacodynamic (PK/PD) and clinical data was used to select a gepotidacin dose for a phase III study. In this narrative review of previously shown data, we summarise how a translational approach based on in vitro PK/PD and population PK modelling and simulation data was undertaken to select a dosing regimen for the ongoing phase III gepotidacin study in participants with uncomplicated urogenital gonorrhoea. Methods: For dose selection, prior in vitro minimum inhibitory concentrations (MICs) and PK/PD data were available. PK modelling was conducted to determine a dose that would limit plasma concentrations to less than 14 µg/mL (as concentrations above this are associated with QT prolongation and effects associated with acetylcholinesterase inhibition) while maintaining ≥90% probability of target attainment (PTA) for efficacy and resistance suppression against N. gonorrhoeae isolates with gepotidacin MICs ≤1 µg/mL. Results: Two 3000 mg gepotidacin doses, administered 10–12 hours apart, resulted in PTA of ≥97.5% and ≥91.7% for gepotidacin MICs ≤1 µg/mL for the ratio of the area under the free drug plasma concentration–time curve over 24 hours to the MIC ( f AUC0–24 /MIC) efficacy, and resistance suppression targets of 40 and 46, respectively, but limited the occurrence of maximum plasma concentrations ≥14 µg/mL. Conclusions: Two gepotidacin 3000 mg oral doses 10–12 hours apart provide ~2-fold higher systemic exposures, increase efficacy for higher gepotidacin MIC N. gonorrhoeae isolates, reduce resistance potential and limit plasma concentrations of potential safety concern, compared with higher doses.